Psycho-Occupational Stress And Its Impact On Mental Health Of Nurses, Laboratory Staff, Pharmacists, And General Physicians (The Review of Diabetic Studies, 2025)
Background: Healthcare workers experience psycho-occupational stress which harms their mental health; however, this has been under-researched across different healthcare disciplines. Aim: The study investigated psycho-occupational stress and mental health consequences among healthcare workers in four categories: nurses, laboratory personnel, pharmacists, and medical doctors. Methods: The study was cross-sectional and quantitative in nature. It comprised 450 healthcare workers (nurses n=145, lab staff n=112, pharmacists n=98, doctors n=95) from five tertiary care hospitals. Participants filled out a self-administered questionnaire which included the Perceived Stress Scale-10 (PSS-10) for work-related stress, the Depression Anxiety Stress Scale-21 (DASS-21) for mental health, and questions for demographic and work-related data. The data were processed using Spearman correlation, descriptive statistics, independent sample t tests, and binary logistic regression in SPSS 26.0.Result: The overall prevalence of depression, anxiety and stress is quantified as 42.4%, 38.9%, and 40.7% respectively. Among the groups, nurses were the most stressed, with an average of 26.3  (5.2) on the PSS-10 ( p < 0.001). The correlation between stress, anxiety and depression was PSS = (26.3, 5.2), (r = 0.658, p < 0.001), (r = 0.621, p < 0.001), (r = 0.712, p < 0.001) respectively. Anxiety was the most present outcome of occupational stress, offering an odds ratio of 2.89, with a 95% confidence interval of (1.78, 4.69) along with depression and stress (r = 3.45, 95% CI: 2.12–5.62) and (r = 4.12, 95% CI: 2.54–6.68). Of the 3,568 participants, Workload 42.7% of the participants stressed; 38.2% were stressed by a lack of recognition, and 35.8 were stressed by staffing shortages.Conclusion: Of the health care professions, nurses, experience the largest magnitude of psycho-occupational stress and, as a consequence, the largest mental health burden. The psycho-occupational stress of mental health within the profession, is a consequence of a lack of organizational change, and improvement in work design, recognition, and staffing.